Studi Literatur: Integrasi Kearifan Lokal dalam Pembelajaran Bilangan Prima, KPK, dan FPB di Sekolah Dasar - Mailani, Elvi; Nur Rarastikab; Fransiska Situmorang; Grace Putri Sigalingging; Yola Adelina Naipospos (CV.ITTC INDONESIA, 2025)
This literature review explores the integration of local wisdom into mathematics learning, with a focus on teaching prime numbers, Least Common Multiple (LCM), and Greatest Common Divisor (GCD) at the elementary level. Mathematics is often perceived by students as abstract and difficult due to the lack of connection to their everyday experiences. Incorporating cultural elements such as traditional games and customary community practices can present mathematical concepts in more contextual and meaningful ways. The findings indicate that culturally based approaches, such as ethnomathematics, enhance students' conceptual understanding and foster appreciation for local traditions. However, challenges remain in implementation, including limited instructional resources and insufficient teacher training. Therefore, collaborative efforts are necessary to develop contextual teaching strategies that reflect local culture, particularly within the context of North Sumatra.